Tumor immune microenvironment in therapy‐naive esophageal adenocarcinoma could predict the nodal status. (25th October 2022) - Kotsafti, Andromachi; Fassan, Matteo; Cavallin, Francesco; Angerilli, Valentina; Saadeh, Luca; Cagol, Matteo; Alfieri, Rita; Pilati, Pierluigi; Castoro, Carlo; Castagliuolo, Ignazio; Scarpa, Melania; Scarpa, Marco
Abstract: Background: Currently, preoperative staging of esophageal adenocarcinoma (EAC) has modest reliability and accuracy for pT and pN stages prediction, which heavily affects overall survival. The interplay among immune checkpoints, oncogenes, and intratumoral and peritumoral immune infiltrating cells could be used to predict loco‐regional metastatic disease in early EAC. Methods: We prospectively evaluated immune markers expression and oncogenes status as well as intratumoral and peritumoral immune infiltrating cells populations in esophageal mucosa samples obtained from neoadjuvant therapy‐naïve patients who had esophagectomy for EAC. Results: Vascular invasion and high infiltration of lamina propria mononuclear cells resulted associated with nodal metastasis. Low infiltration of activated CD8 + CD28 + T cells was observed in both intratumoral and peritumoral mucosa of patients with nodal metastasis. Low levels of CD69, MYD88, and TLR4 transcripts were detected in the intratumoral specimen of patients with lymph node involvement. Receiver operating characteristic curve analysis showed good accuracy for detecting nodal metastasis for all the markers tested. Significant lower infiltration of CD8 T cells and M1 macrophages and a lower expression of CD8A, CD8B, and TBX21 were found also in Esophageal Adenocarcinoma TCGA panCancer Atlas in the normal tissue of patients with nodal metastasis. Conclusions: Our data suggest that immune surveillance failure is the main driver of nodal metastasis onset. Moreover, nodal metastasis containment also involves the immune microenvironment of the peritumoral healthy tissue. Abstract : Low infiltration of activated CD8 + CD28 + T cells was observed in both intratumoral and peritumoral mucosa of patients with nodal metastasis suggesting that immune surveillance failure is the main driver of nodal metastasis onset.